Correction: Dong et al. Possible Shifts in the Genetic Diversity of Red-crowned Cranes (Grus japonensis) in Hokkaido, Japan: Indications of Continental Gene Flow. Animals 2024, 14, 1633 - Wenjing Dong; Kai Tomita; Akira Sawada; Makoto Hasebe; Masako Inoue; Kunikazu Momose; Tatsuro Nakamura; Hiroki Teraoka (Animals)
In the original publication [...]